First report of the carnivorous sponge Lycopodina hypogea (Cladorhizidae) associated with marine debris, and its possible implications on deep-sea connectivity - Santín, A.; Grinyó, J.; Bilan, M.; Ambroso, S.; Puig, P. (Marine Pollution Bulletin, 2020)
Nowadays, there are an increasing number of reports of deep-sea accumulation of marine debris, often associated with a wide array of pernicious effects on benthic fauna. Nevertheless, there is still a huge knowledge gap regarding the interaction of benthic organisms and marine debris. In this paper, we report for the first time the colonization of plastic debris by the protected sponges Lycopodina hypogea. The sponges were discovered growing on plastic debris tangled with nylon ropes on the Blanes canyon (northwestern Mediterranean Sea). Over 30 individuals of L. hypogea were identified attached on ca. 10 cm2 plastic debris, an unusual feature for a species mostly known for low-density populations and a patchy distribution. The implications of this discovery are discussed, and it is suggested that marine debris might provide substrate for benthic species on otherwise unsuitable habitats, with its possible role as stepping-stones for deep-sea benthic connectivity needing further study.